Experimental investigation of freeze-thaw environmental effects on the fatigue life of CFRP composites - Jeong Hwan Kim; Dongwon Ha; Min-Sung Kim; Gun Jin Yun (Polymer Testing)
This paper investigates the effect of Freeze-Thaw (FT) environments on the fatigue behavior of carbon fiber-reinforced polymer (CFRP) composites under extreme conditions. The effect of FT cycles on CFRP fatigue life has not been previously studied. In this paper, three types of specimens (open-hole, transverse, and shear) were subjected to FT cycles: freezing at −60 °C and thawing at 30 °C. Open-hole specimens (OHS) were subjected to 0, 50, and 100 FT cycles before being tested at stress ratios R = 10 and R = −1, while transverse (TS) and shear specimens (SS) were exposed to 0 and 100 FT cycles and tested under R = −1. Fracture surfaces were analyzed using Scanning Electron Microscopy (SEM). SEM observations revealed that the FT cyclic environment weakened the fiber-matrix bond across all specimens. However, the fatigue life of CFRP is primarily governed by dominant failure mechanisms, which depend on the stress ratio and laminate configuration. In SS, where fiber-matrix debonding is the primary failure mechanism, the FT environment directly affected fatigue life, significantly reducing fatigue resistance. In contrast, the fatigue life of OHS and TS was predominantly determined by the specific failure mechanisms characteristic of each laminate rather than being directly influenced by the FT environment.